Subjective cognitive deficits and its correlates among patients with bipolar disorder: Findings from the bipolar disorder course and outcome study from India (BiD-CoIN study) - Sandeep Grover; Ajit Avasthi; Rahul Chakravarty; Amitava Dan; Kaustav Chakraborty; Rajarshi Neogi; Avinash Desouza; Omkar Nayak; Samir Praharaj; Vikas Menon; Raman Deep; Manish Bathla; et al. (Indian Journal of Psychiatry)
Aim: This study aimed to evaluate the prevalence of subjective cognitive complaints and their association with clinical variables, insight, and disability. Methodology: Seven hundred and seventy-three subjects with bipolar disorder (BD), recruited across 14 centers, currently in the euthymic phase were cross-sectionally evaluated on Cognitive Complaints in Bipolar Disorder Rating Assessment (COBRA). Results: The mean total COBRA score was 9.79 (SD: 6.99), and 322 (41.7%) of the participants were found to have subjective cognitive complaints when the cut-off of >10 was used. Compared to those without cognitive complaints, those with cognitive complaints more often had depression as the first episode in their lifetime, had a higher prevalence of alcohol dependence, a higher number of depressive episodes (first five years of illness, lifetime, and per year of illness), a higher number of manic episodes in the first five years of illness, more often had depressive or indeterminate predominant polarity, lower prevalence of at least one-lifetime episode with psychotic symptoms, higher severity of residual symptoms, spent more time in the episodes in the lifetime, had poorer insight and higher disability. Conclusion: The present study suggests subjective complaints complaints are associated with more severe illness, higher levels of residual symptoms, poor insight, and higher disability.